First evidence of association between past environmental exposure to dioxin and DNA methylation of CYP1A1 and IGF2 genes in present day Vietnamese population. (November 2018) - Giuliani, Cristina; Biggs, David; Nguyen, Thanh Tin; Marasco, Elena; De Fanti, Sara; Garagnani, Paolo; Le Phan, Minh Triet; Nguyen, Viet Nhan; Luiselli, Donata; Romeo, Giovanni
Abstract: During the Vietnam War, the United States military sprayed over 74 million litres of Agent Orange (AO) to destroy forest cover as a counterinsurgency tactic in Vietnam, Laos and Cambodia. The main ingredient was contaminated by 2, 3, 7, 8-tetrachlorodibenzo-paradioxin (TCDD). DNA methylation (DNAm) differences are potential biomarker of environmental toxicants exposure. The aim of this study was to perform a preliminary investigation of the DNAm levels from peripheral blood of the present-day Vietnamese population, including individuals whose parents, according to historical data, were exposed to AO/TCDD during the war. 94 individuals from heavily sprayed areas (cases) and 94 individuals from non-sprayed areas (controls) were studied, and historical data on alleged exposure of parents collected. 94 cases were analysed considering those whose father/parents participated in the war (N = 29) and considering the place of residence of both parents (64 living in sprayed areas versus 30 in non-contaminated areas). DNAm levels in CYP1A1 and IGF2 genes were measured (MALDI-TOF technology). The analyses showed that: 1) one CpG site in the CYP1A1 and one in the IGF2 gene showed significant differences in DNAm levels between cases and controls; 2) the CYP1A1 region resulted to be hypomethylated (in 9 out of 16 sites/units; p-val<0.01) in 29 individuals whose father/parents participated in the war in the spray zones; 3) we showed that the place of residence of both parents influenced methylation levels of the CYP1A1 and IGF2 genes (p-val<0.05). In conclusion this study indicates that past environmental exposure to dioxin (AO/TCDD) shapes the DNAm profile of CYP1A1 and that the place of living for parents in former spray zones influences DNAm of CYP1A1 and IGF2 genes. These results open the way to new applications of DNAm as potential biomarker(s) of past human exposure to dioxin. Graphical abstract: Image 1 Highlights: Living in dioxin sprayed areas (Vietnam War) minimally affects DNA methylation (CYP1A1 and IGF2) in present-day Vietnamese. Changes in DNA methylation of CYP1A1 are observed in individuals whose parents participated in the war in the spray zones. DNA methylation of CYP1A1 and IGF2 genes of present-day Vietnamese population is shaped by their parents place of living. Integrating historical data and DNA methylation profile opens the way for new biomarkers for past environmental changes. Abstract : This gene-candidate study on 188 individuals from a Vietnamese population indicates that past environmental exposure to dioxin (AO/TCDD) shapes the DNA methylation profile of regions in CYP1A1 gene and that the place of living of parents in former spray zones influences DNA methylation of CYP1A1 and IGF2 genes in the offspring.